The interactions between different types of financial and human resource slacks on firm performance: Evidence from a developing country - M. M. Fonseka; G-L. Tian; X. Yang; R. L.T.N. Rajapakse (South African Journal of Business Management, 2014)
This paper investigates the effect of both FS and HR slack together on firm performance and how different levels of these slack resources affect performance of private-owned enterprises (POEs) and state-owned enterprises (SOEs). Hypotheses are tested using a longitudinal data set of 11,985 listed Chinese companies from 2000 to 2009. Findings reveal that the unabsorbed-financial slack and HR slack show an inverse U shape relationship on firm performance for both POEs and SOEs. However, a less-negative interaction occurs for unabsorbed-financial and HR slacks for POEs. The absorbedfinancial and HR slacks also shows an inverse U shape relationship on performance and this relationship does not have a significant negative effect on SOE's performance. The article concludes with theoretical contributions and practical implications of the findings.
Keywords: 650